Impact of higher education on income and economic growth : a cross country evidence - Lai, Wei Sieng; Ishak Yussof, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Education is commonly used as indicator for human capital and can be divided into three levels: primary, secondary and tertiary. Each level of education designed with different skills and knowledges for population from different ages and hence produce human capital stock with different quality. Higher education leads to higher individual income or earning and thus contribute to income and economic growth. Middle income nations are investing less in higher education compared to high income nations in higher education. This study provides evidence on the impact of higher education on income and economic as a reference to middle income nations. This study applies dynamic panel data using PMG method and data from 2000 to 2015 for 30 high income countries. Empirical results suggest that tertiary education have positive and significant impact on income and economic growth. Besides, investment on nonfinancial assets, household consumption and trade openness also contribute positively on income growth. The result of this study suggest that government should allocate more fund on expansion of higher education in order to produce more labor with higher education, particularly middle income nations which aiming at achieving high income nation’s status.